Pengaruh Kepemimpinan Kepala Sekolah, Motivasi Kerja, dan Budaya Sekolah Terhadap Kinerja Guru - Setiyati, Sri (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objective of this study was to determine: (1) the influence of principals’ leadership, work motivation, and school culture on the performance of State Vocational High School teachers in Gunungkidul Regency, (2) the influence of principal’s leadership on the teachers’ performance (3) the influence of job motivation on the teachers’ performance, (4) the influence of school culture on the teachers’ performance. The study was a quantitative descriptive study. The population of the study were 753 teachers of State Vocational High School teachers in Gunungkidul regency. The results of the data analysis showed (1) there is positive and very significant influence of the principal’s leadership, work motivation, and school cultures on the teachers’ performance with the percentage of 42,2 % (2) there is positive and very significant influence of the of principal’s leadership on the teacher’s performance with the percentage of 18,22% (3) there is positive and very significant influence of work motivation on the teachers’ performance with the percentage of 13,03% (4) there is positive and very significant influence of school culture on the teachers’ performance with the percentage of 10,94%.